2002
DOI: 10.1046/j.1523-1739.2002.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Nest Predators and Fragmentation: a Review and Meta‐Analysis

Abstract: Population declines of many avian species are often attributed to increased rates of nest predation in fragmented landscapes, yet mechanisms underlying these effects have rarely been examined. We reviewed the literature to determine the extent to which hypotheses about nest predators and fragmentation have been invoked and compared this to the number of direct tests of predators with respect to habitat edge, patch size, or landscape type. We also conducted a meta‐analysis of tested predator effects to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
398
3
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 489 publications
(439 citation statements)
references
References 116 publications
21
398
3
17
Order By: Relevance
“…Thus, patterns of increased nest predation in small fragments are inconsistent with a hypothesis of increased rodent abundance. A recent review of studies examining the impact of fragmentation on nest predators in temperate regions found that avian predators and snakes were likely to be more abundant, more active, or more species-rich in small patches and along edges than rodents (26), and thus we suspect that increased rates of nest predation in small fragments are probably a result of increased abundance and/or activity of nonrodent nest predators in small fragments in our study system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, patterns of increased nest predation in small fragments are inconsistent with a hypothesis of increased rodent abundance. A recent review of studies examining the impact of fragmentation on nest predators in temperate regions found that avian predators and snakes were likely to be more abundant, more active, or more species-rich in small patches and along edges than rodents (26), and thus we suspect that increased rates of nest predation in small fragments are probably a result of increased abundance and/or activity of nonrodent nest predators in small fragments in our study system.…”
Section: Discussionmentioning
confidence: 90%
“…Over the course of the study we observed a diverse community of predators, comprising raptors, snakes, rodents, and ants, preying on eggs and young. Although the composition and response of the predator community to habitat fragmentation will ultimately influence spatial patterns of avian nest survival (3), our understanding of the impact of fragmentation on nest predator communities is limited (25,26) and particularly so in the tropics. It has been suggested that landscape structure and nest location may mediate nest predation risk via changes in predator abundance and/or behavior (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Importance of edge contrast varies across scales and may be less important for wildlife than more complex measures of heterogeneity, interactions among multiple metrics, or fragmentation (e.g., Hansson et al 1995, Bolger et al 2000, Kie et al 2002, Rodewald 2002. However, few studies exist on edge contrasts for relatively small wildlife species in chaparral habitats (e.g., Langen et al 1991, Crooks and Soulé 1999, Bolger et al 2000) as compared to forests (Chalfoun et al 2002).…”
Section: Presence Of Species Affected (mentioning
confidence: 99%
“…Esses resultados mostraram que os ninhos de E. chiriquensis que estavam na borda e no interior podem ter sofrido pressões de diferentes predadores, provavelmente devido a diferenças na distribuição e/ou na abundância dos mesmos (CHALFOUND et al 2002). Os censos demonstraram que para duas espécies comuns de predadores, a abundância é semelhante na borda e no interior.…”
Section: Parasitismo De Ninhosunclassified
“…Os censos demonstraram que para duas espécies comuns de predadores, a abundância é semelhante na borda e no interior. Uma revisão de trabalhos que mencionavam hipóteses sobre predadores de ninhos e fragmentação ou efeito de borda revelou que a resposta dos predadores à fragmentação é complexa, taxon-específica, dependente do contexto, e, além disso, em 76% dos casos, os testes não apresentaram efeito significativo (CHALFOUND et al 2002).…”
Section: Parasitismo De Ninhosunclassified